2013
DOI: 10.1371/journal.pone.0075983
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Response of Alveolar Macrophage to House Dust Mite Allergen Is Mediated through TLR2/-4 Co-Activation

Abstract: House dust mite, Dermatophagoides pteronyssinus (Der p), is one of the major allergens responsible for allergic asthma. However, the putative receptors involved in the signalization of Der p to the innate immune cells are still poorly defined as well as the impact of their activation on the outcome of the allergen-induced cell response. We previously reported that the HDM activation of mouse alveolar macrophages (AM) involves the TLR4/CD14 cell surface receptor complex. Here using a TLR ligand screening essay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…3, MH-S cells produce and release IL-6 and CXCL-10 in response to synthetic ligands for the pattern recognition receptors TLR2 and NOD2, as well as in response to challenge with heat-inactivated Gram-positive Lactobacillus reuteri. Although MH-S cells have been previously shown to express TLR2 [8], this is the first report that documents responses consistent with expression of the intracellular pattern recognition receptor NOD2. Like TLR2, NOD2 recognizes pathogen associated molecular patterns (PAMPs), which leads to transcription of NF-kB-dependent gene targets [40].…”
Section: 0 Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3, MH-S cells produce and release IL-6 and CXCL-10 in response to synthetic ligands for the pattern recognition receptors TLR2 and NOD2, as well as in response to challenge with heat-inactivated Gram-positive Lactobacillus reuteri. Although MH-S cells have been previously shown to express TLR2 [8], this is the first report that documents responses consistent with expression of the intracellular pattern recognition receptor NOD2. Like TLR2, NOD2 recognizes pathogen associated molecular patterns (PAMPs), which leads to transcription of NF-kB-dependent gene targets [40].…”
Section: 0 Results and Discussionmentioning
confidence: 98%
“…Adherent cells from bronchoalveolar lavage of BALB/cJ mice were infected with Simian Virus (SV)-40; the resulting immortalized cells expressed the surface receptors Mac-1 (CD11b/CD18) and produced IL-1 in response to lipopolysaccharide (LPS) stimulation. Recent reports on this cell line note constitutive expression of pattern recognition receptors (PRRs) toll-like receptor (TLR)2 and TLR4 [8], and the ability to phagocytose latex beads [9]. …”
Section: 0 Introductionmentioning
confidence: 99%
“…critical to the development of a type-2 immune response (15)(16)(17)(18)(19)(20). Thus far, there has been little evidence implicating sPLA 2 -X as a regulator of these responses; however, a recent paper examining the effect of bee venom PLA 2 (bvPLA 2 ) in the periphery demonstrated that bvPLA 2 induces the release of IL-33, leading to the generation of ILC2s and subsequent antigen-specific T cell responses (21).…”
Section: Introductionmentioning
confidence: 99%
“…Der p is known to express major IgE-binding proteins, with unknown biological functions, and exposure to Der p can increase IgE production and stimulate T cell proliferation. 6 Der p induce Th 2 cells to release interleukin (IL)-4, IL-5, and IL-13 7,8 to increase the production of inflammatory cells, including neutrophils, macrophages, mast cells, and eosinophils, as well as infiltration, cytokines (IL-6 and IL-8), smooth muscle cell proliferation, and mucus production in allergic asthma. The possible mechanism is that dendritic cells (DCs) synthesize IL-12 efficiently and are potent inducers of Th1 immune responses in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…5 The possible mechanisms are that Der p interact with T cell receptors (TCRs) to activate phospholipase D (PLD), which activates Th 2 cell responses. 6 Der p induce Th 2 cells to release interleukin (IL)-4, IL-5, and IL-13 7,8 to increase the production of inflammatory cells, including neutrophils, macrophages, mast cells, and eosinophils, as well as infiltration, cytokines (IL-6 and IL-8), smooth muscle cell proliferation, and mucus production in allergic asthma. These responses cause airway inflammation and remodeling, resulting in the development of asthma.…”
mentioning
confidence: 99%